2007
DOI: 10.1183/09031936.00156906
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator-associated pneumonia due to colistin susceptible-only microorganisms

Abstract: Acinetobacter spp. and Pseudomonas aeruginosa are common pathogens of ventilator-associated pneumonia (VAP). The presentation and outcome of VAP due to Acinetobacter spp. and P. aeruginosa susceptible to carbapenems (Carb-S; imipenem and/or meropenem) and to colistin only (Col-S) were compared in the present retrospective study in three intensive care units.A total of 61 episodes of VAP caused by Acinetobacter spp. or P. aeruginosa were studied, of which 30 isolates were Carb-S and 31 were Col-S.Demographics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 32 publications
3
43
1
3
Order By: Relevance
“…According to our results, we had 50 Carb-S and only six Col-S isolates, which is a significant difference compared with the study by RIOS et al [1]. Also, only eight of the 50 Carb-S isolates were sensitive to imipenem but all 50 were meropenem sensitive (Mer-S).…”
supporting
confidence: 37%
See 1 more Smart Citation
“…According to our results, we had 50 Carb-S and only six Col-S isolates, which is a significant difference compared with the study by RIOS et al [1]. Also, only eight of the 50 Carb-S isolates were sensitive to imipenem but all 50 were meropenem sensitive (Mer-S).…”
supporting
confidence: 37%
“…Also, only eight of the 50 Carb-S isolates were sensitive to imipenem but all 50 were meropenem sensitive (Mer-S). Another difference with that study [1] is that 41 gentamicin-sensitive (Gent-S) isolates were identified.…”
mentioning
confidence: 69%
“…polymyxins (colistin and polymyxin B), an antibiotic class discovered more that 60 years ago that had been abandoned for nearly 20 years, except for in the distinct population of patients with cystic fibrosis [2]. A number of recently published clinical studies have suggested that colistin may be considered in the treatment of patients with MDR Gram-negative bacterial infections [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This resistance profile lead in most of case, to using polymixine E (colistine) as the only efficient drug given by parenteral route and by aerosol to the MDRB infections especially Acinetobacter and Enterobacteriaceae producing carbapenemases [49][50][51][52]. Therefore, we recorded an increase incidence of bacterial species that are naturally resistant to polymyxin E (Proteus, Providencia, Serratia and Corynebacteria especially, multi-resistant one: Corynebacterium striatum).…”
Section: Discussionmentioning
confidence: 97%